Effects of γ-PGA application on soil physical and chemical properties, rhizosphere microbial community structure and metabolic function of urban abandoned land - Shiheng, Tu; Fanglan, Ge; Yong, Xu; Qingyi, Sun; Fugui, Xie; Yao, Ren; Juan, Du; Can, Chu; Boyuan, Xu; Wei, Li (Frontiers in Microbiology, 2025)
IntroductionChina’s rapid urbanization has led to the conversion of extensive farmland on urban fringes into non-grain uses, exacerbating the scarcity of arable land resources. Reclaiming these abandoned or underutilized areas presents a viable solution. However, many of these lands are contaminated with construction debris and have uneven soil quality, rendering them unsuitable for crop cultivation. This study aims to investigate the effects of γ-polyglutamic acid (γ-PGA) on improving such soils.MethodsA 6-month field experiment was conducted on green spaces with mixed construction waste in Chengdu’s urban ring. The study analyzed the impact of γ-PGA on soil bacterial communities, metabolites, and physicochemical properties during different wheat growth stages, namely tillering, jointing, flowering, and maturity.Resultsγ-PGA significantly increased soil organic matter, total nitrogen, nitrate nitrogen, and alkali-hydrolyzable nitrogen. It also boosted enzyme activities such as urease, sucrase, and alkaline phosphatase. The soil mechanical structure improved, with increases in clay, sand, and macroaggregates. As wheat grew, the fractal dimensions of soil volume and infiltration performance increased, while bulk density decreased, indicating enhanced water retention and gas exchange. Beneficial microorganisms like Actinobacteria and Devosia increased in abundance, promoting soil fertility. Metabolomics analysis revealed that γ-PGA enriched pathways involved in carbohydrate digestion, starch metabolism, and nucleotide processes, creating a more favorable environment for plant growth.DiscussionThis research underscores the crucial role of γ-PGA in soil restoration and fertility enhancement. The findings provide valuable insights for reclaiming non - grain farmland, offering a potential solution to the challenge of arable land shortage caused by urbanization. The study’s results contribute to the existing knowledge on soil improvement techniques and have practical implications for sustainable agricultural development in urbanized regions. However, further research could explore the long-term effects of γ-PGA application and its applicability in different soil types and environmental conditions.